The PENILAIAN KINERJA DOSEN DENGAN METODE FUZZY MAMDANI DI AMIK CBI SUKABUMI - wawang Adi Darma (BUANA INFORMATIKA, 2016)
An assessment of faculty performance are (1) the process of assessing how a person has worked compared to predetermined targets. (2) the process of documenting measurement, knowledge, skills, attitudes, and beliefs on the individual learner or groups of people, institutions, or the education system as a whole. GAP Analysis and Fuzzy Logic models Mamdani is a form of analysis and methods used in assessing faculty performance on AMIK Citra Buana Indonesia (CBI) Sukabumi. Analysis is conducted an analysis of the difference (gap) between the assessment by students and faculty performance and assessment standards institutes of some indicators of assessment, namely productivity, quality of work, problem solving and motivation and responsibility. Steps being taken in mamdani fuzzy methods are (a). Fuzzification. (B). Apps function implications (c). The composition of the rules with maximum method. (D). Centroid defuzzification method. The results of the research faculty performance assessment is fairly accurate with the difference between the appraisal value of 0.6 to the fuzzy method mamdani and use conventional methods that have been carried out by the institution.